Exposure to climate-change related extreme weather events and risk preferences: evidence from farmers in Central Highland Afghanistan - Jawid, Asadullah; Khadjavi, Menusch (Frontiers in Behavioral Economics, 2025)
We study whether long-term exposure to climate-change-related extreme weather events is associated with farmers' risk preferences. We combine (i) a household survey of 1,502 farmers across 14 districts in Afghanistan's Central Highlands with (ii) an incentivized lab-in-the-field risk task for 239 farmers, and (iii) farm-level GPS coordinates that proxy drought exposure via distance to rivers/streams. Our analysis shows that farmers in (very) high-exposure locations are systematically less risk-averse: exposure predicts choosing riskier gambles in the Eckel–Grossman task and reporting greater willingness to take risks. Plausibility checks using GPS distances corroborate self-reported exposure. We discuss mechanisms consistent with adaptation to a persistently riskier environment and with background risk dampening aversion to additional independent risks. Our findings highlight that climate change can alter economic preferences themselves, with implications for adaptation policy design (e.g., uptake of new seeds, irrigation, or insurance).